2018
DOI: 10.1016/j.chempr.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Photoactivatable Oxygenation Catalysts of Amyloid Peptide

Abstract: A biocompatible photooxygenation catalyst that can selectively oxygenate and degrade the pathogenic aggregation of Alzheimer's disease (AD)-related amyloid-b peptide (Ab) under near-infrared light irradiation has been developed. The catalyst oxygenates Ab embedded under the skin of a living mouse and diminishes the intact Ab level in an AD-model mouse brain. The new catalyst is potentially applicable for the treatment of peripheral amyloid diseases and AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 38 publications
2
59
0
1
Order By: Relevance
“…53,54 Photo-oxygenating Ab is capable of disintegrating Ab aggregates through increasing the protein polarity, which is an attractive strategy for AD therapy. [55][56][57][58] However, in the presence of Cu, just oxygenating Ab may not entirely block its brillation because Cu can still promote protein aggregation by coordinating to Ab. Considering that Cu and Ab are two critical pathogenic factors of AD, 59,60 we envisioned that in situ synthesized bifunctional drug agent with Ab-oxygenating and Cu-chelating properties could effectively disassemble Ab-Cu aggregates in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 Photo-oxygenating Ab is capable of disintegrating Ab aggregates through increasing the protein polarity, which is an attractive strategy for AD therapy. [55][56][57][58] However, in the presence of Cu, just oxygenating Ab may not entirely block its brillation because Cu can still promote protein aggregation by coordinating to Ab. Considering that Cu and Ab are two critical pathogenic factors of AD, 59,60 we envisioned that in situ synthesized bifunctional drug agent with Ab-oxygenating and Cu-chelating properties could effectively disassemble Ab-Cu aggregates in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…S15 †). 55,61 Ab40 (10 mM) and compound 6 (20 mM) were irradiated with UV light (1 W cm À2 ) for 1 h and then photooxygenated Ab was detected by MS. Fig. S16 † illustrates that both compounds 4 and 6 can effectively oxygenate Ab40.…”
Section: Resultsmentioning
confidence: 99%
“…To solve this issue, chemical strategies have also been applied to suppress Aβ aggregation and downstream toxicity for AD treatment. Although inconsistent and even contradictory to the discussed antioxidative therapy, several reports have indicated that the oxidative modification of Aβ peptides may contribute to the inhibition of Aβ aggregation and the improvement of AD treatment . These efforts involve the harvesting of external optical energy to activate photocatalysts and facilitate ROS generation in pathological region, thus acquiring therapeutic effect.…”
Section: Nanocatalytic Medicine For Nontumoral Therapiesmentioning
confidence: 99%
“…The cytotoxicity of the RB-treated Aβ42 peptides was also remarkably reduced compared with the untreated one. Similar lightinduced inhibition was also reported using ruthenium (II) complex[168], porphyrins[21], carbenoxolone[169] and CRANAD-2 derivatives[170]. For in vivo studies, light penetration is a challenge in order to achieve the needed light-induced inhibition.…”
supporting
confidence: 63%
“…By introducing a bromine atom into an amyloid dye, CRANAD-2, they created a photoactivatable oxygenation catalyst that can be turned on under NIR irradiation. The tissue permeability of NIR light makes it possible to function under mouse skin and even inside mouse brains[170].…”
mentioning
confidence: 99%